Understanding the mechanism of direct visible-light-activated [2 + 2] cycloadditions mediated by Rh and Ir photocatalysts: combined computational and spectroscopic studies. Issue 28 (23rd June 2021) - Jung, Hoimin; Hong, Mannkyu; Marchini, Marianna; Villa, Marco; Steinlandt, Philipp S.; Huang, Xiaoqiang; Hemming, Marcel; Meggers, Eric; Ceroni, Paola; Park, Jiyong; Baik, Mu-Hyun
Abstract : The mechanism of [2 + 2] cycloadditions activated by visible light and catalyzed by bis-cyclometalated Rh(iii ) and Ir(iii ) photocatalysts was investigated, combining density functional theory calculations and spectroscopic techniques. Abstract : The mechanism of [2 + 2] cycloadditions activated by visible light and catalyzed by bis-cyclometalated Rh(iii ) and Ir(iii ) photocatalysts was investigated, combining density functional theory calculations and spectroscopic techniques. Experimental observations show that the Rh-based photocatalyst produces excellent yield and enantioselectivity whereas the Ir-photocatalyst yields racemates. Two different mechanistic features were found to compete with each other, namely the direct photoactivation of the catalyst–substrate complex and outer-sphere triplet energy transfer. Our integrated analysis suggests that the direct photocatalysis is the inner working of the Rh-catalyzed reaction, whereas the Ir catalyst serves as a triplet sensitizer that activates cycloaddition via an outer-sphere triplet excited state energy transfer mechanism.